Evaluación del agua gravitacional a través del perfil de un suelo de la altillanura - Valenzuela, I.G.; Perea, G; Amézquita Collazos, Edgar (2001)
With the purpose of determining under field conditions the quantity of rainfall that moves vertically to several depths in the Altillanura, a soil Tipyc Haplustox isohipertérmico caolinítico of the municipality of Port López (Meta) was selected, worked during several years (2, 4 and 6 trail passes per year for a total accumulated to the moment of the tests of 8, 16 and 32 passes) and different handling conditions (native Savanna; Rice (with 8 and 16 trail passes) and I Pasture (B. Dictyoneura with 16 and 32 trail passes)). It was evaluated in situ the quantity of rain that passes through different depths of the soil using funnel microlisímetros installed to the following depths: 3 cm, 5 cm, 10 cm, 15 cm, 20 cm and 30 cm. To each depth the volume of water was measured that it went by each soil sheet and the soluble components were determined (NO3, Ca, K, P), pH and electric Conductivity. Additionally the quantity of rain weekly fall was determined in the work area, to establish the existent relationship between the precipitation and the quantity of water that it went by each depth. There was high variability in the form which water moves inside the soil, in which is affected by the preferential flow. The quantity of soluble components that move from a layer to another being function of the quantity of water that passes. For the soils of the Altillanura it was found that the grasses allow a better distribution of water and nutritious since they create and they maintain macroporos improving the physical state of the soil.